If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5r + 3f)(5r + -3f) = 0 Reorder the terms: (3f + 5r)(5r + -3f) = 0 Reorder the terms: (3f + 5r)(-3f + 5r) = 0 Multiply (3f + 5r) * (-3f + 5r) (3f * (-3f + 5r) + 5r * (-3f + 5r)) = 0 ((-3f * 3f + 5r * 3f) + 5r * (-3f + 5r)) = 0 Reorder the terms: ((15fr + -9f2) + 5r * (-3f + 5r)) = 0 ((15fr + -9f2) + 5r * (-3f + 5r)) = 0 (15fr + -9f2 + (-3f * 5r + 5r * 5r)) = 0 (15fr + -9f2 + (-15fr + 25r2)) = 0 Reorder the terms: (15fr + -15fr + -9f2 + 25r2) = 0 Combine like terms: 15fr + -15fr = 0 (0 + -9f2 + 25r2) = 0 (-9f2 + 25r2) = 0 Solving -9f2 + 25r2 = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-25r2' to each side of the equation. -9f2 + 25r2 + -25r2 = 0 + -25r2 Combine like terms: 25r2 + -25r2 = 0 -9f2 + 0 = 0 + -25r2 -9f2 = 0 + -25r2 Remove the zero: -9f2 = -25r2 Divide each side by '-9'. f2 = 2.777777778r2 Simplifying f2 = 2.777777778r2 Take the square root of each side: f = {-1.666666667r, 1.666666667r}
| 4(h-3)-13h=-13+1 | | 11-6-2= | | 3(3a-2)=2(3m+3) | | 8+6*(4-3)*8= | | -75(x-20)=x+(-22) | | x-5+10=-5 | | h=-6t^2-15t+50 | | 3ysquared+2=14 | | Kx+kx+9=0 | | 7x-3=3x+15 | | 4-(-h)=88 | | 26-2v=5(v-6)+v | | 6(x+3)=39-x | | 6(4-x)+6=24 | | exp(2x)-5=0 | | 6-6(6n-2)=18-4n | | 14mn+11= | | 2a-5b=8 | | x-2(x+10)=x+12 | | H-10=-12 | | 4-(-28)=0 | | 3(x-2)+2=3x-8 | | m-2.45=13 | | 7x+7=(-5x-5) | | -9x-2=34 | | 2x+3(x-5)=100 | | 4x^2+y^2-40x+2y-85=0 | | 16x+kx+25=0 | | 9x-4+6=-4 | | 6(x-1)=6x-3 | | -8+p/8=-7 | | 75(x+7)=11025 |